Brain Targeting, Antioxidant Polymeric Nanoparticles for Stroke Drug Delivery and Therapy. Issue 22 (20th March 2022) - Wu, Haoan; Peng, Bin; Mohammed, Farrah S.; Gao, Xingchun; Qin, Zhenpeng; Sheth, Kevin N.; Zhou, Jiangbing; Jiang, Zhaozhong
Abstract: Ischemic stroke is a leading cause of death and disability and remains without effective treatment options. Improved treatment of stroke requires efficient delivery of multimodal therapy to ischemic brain tissue with high specificity. Here, this article reports the development of multifunctional polymeric nanoparticles (NPs) for both stroke treatment and drug delivery. The NPs are synthesized using an reactive oxygen species (ROS)‐reactive poly (2, 2′‐thiodiethylene 3, 3′‐thiodipropionate) (PTT) polymer and engineered for brain penetration through both thrombin‐triggered shrinkability and AMD3100‐mediated targeted delivery. It is found that the resulting AMD3100‐conjugated, shrinkable PTT NPs, or ASPTT NPs, efficiently accumulate in the ischemic brain tissue after intravenous administration and function as antioxidant agents for effective stroke treatment. This work shows ASPTT NPs are capable of efficient encapsulation and delivery of glyburide to achieve anti‐edema and antioxidant combination therapy, resulting in therapeutic benefits significantly greater than those by either the NPs or glyburide alone. Due to their high efficiency in brain penetration and excellent antioxidant bioactivity, ASPTT NPs have the potential to be utilized to deliver various therapeutic agents to the brain for effective stroke treatment. Abstract : This study develops nanoparticles (NPs) consisting of a reactive oxygen species (ROS)‐reactive polymer and further engineers them for targeted drug delivery to the ischemic brain through ligand‐mediated interaction and thrombin‐triggered shrinkability. It is demonstrated that the resulting NPs can efficiently deliver glyburide to the brain for effective stroke treatment.